Experiences of mental illness stigma, prejudice and discrimination: a review of measures - Clement Sarah; Slade Mike; Brohan Elaine; Thornicroft Graham (BMC, 2010)
Abstract Background There has been a substantial increase in research on mental illness related stigma over the past 10 years, with many measures in use. This study aims to review current practice in the survey measurement of mental illness stigma, prejudice and discrimination experienced by people who have personal experience of mental illness. We will identify measures used, their characteristics and psychometric properties. Method A narrative literature review of survey measures of mental illness stigma was conducted. The databases Medline, PsychInfo and the British Nursing Index were searched for the period 1990-2009. Results 57 studies were included in the review. 14 survey measures of mental illness stigma were identified. Seven of the located measures addressed aspects of perceived stigma, 10 aspects of experienced stigma and 5 aspects of self-stigma. Of the identified studies, 79% used one of the measures of perceived stigma, 46% one of the measures of experienced stigma and 33% one of the measures of self-stigma. All measures presented some information on psychometric properties. Conclusions The review was structured by considering perceived, experienced and self stigma as separate but related constructs. It provides a resource to aid researchers in selecting the measure of mental illness stigma which is most appropriate to their purpose.